Dental therapists compared with general dental practitioners for undertaking check-ups in low-risk patients: pilot RCT with realist evaluation - Paul Brocklehurst; Zoe Hoare; Chris Woods; Lynne Williams; Andrew Brand; Jing Shen; Matthew Breckons; James Ashley; Alison Jenkins; Lesley Gough; Philip Preshaw; Christopher Burton; et al. (National Institute for Health Research, 2021)
Background: Many dental 'check-ups' in the NHS result in no further treatment. The patient is examined by a dentist and returned to the recall list for a further check-up, commonly in 6 or 12 months' time. As the oral health of regular dental attenders continues to improve, it is likely that an increasing number of these patients will be low risk and will require only a simple check-up in the future, with no further treatment. This care could be delivered by dental therapists. In 2013, the body responsible for regulating the dental profession, the General Dental Council, ruled that dental therapists could see patients directly and undertake check-ups and routine dental treatments (e.g. fillings). Using dental therapists to undertake check-ups on low-risk patients could help free resources to meet the future challenges for NHS dentistry. Objectives: The objectives were to determine the most appropriate design for a definitive study, the most appropriate primary outcome measure and recruitment and retention rates, and the non-inferiority margin. We also undertook a realist-informed process evaluation and rehearsed the health economic data collection tool and analysis. Design: A pilot randomised controlled trial over a 15-month period, with a realist-informed process evaluation. In parallel, we rehearsed the health economic evaluation and explored patients' preferences to inform a preference elicitation exercise for a definitive study. Setting: The setting was NHS dental practices in North West England. Participants: A total of 217 low-risk patients in eight high-street dental practices participated. Interventions: The current practice of using dentists to provide NHS dental check-ups (treatment as usual; the control arm) was compared with using dental therapists to provide NHS dental check-ups (the intervention arm). Main outcome measure: The main outcome measure was difference in the proportion of sites with bleeding on probing among low-risk patients. We also recorded the number of 'cross-over' referrals between dentists and dental therapists. Results: No differences were found in the health status of patients over the 15 months of the pilot trial, suggesting that non-inferiority is the most appropriate design. However, bleeding on probing suffered from 'floor effects' among low-risk patients, and recruitment rates were moderately low (39.7%), which suggests that an experimental design might not be the most appropriate. The theory areas that emerged from the realist-informed process evaluation were contractual, regulatory, institutional logistics, patients' experience and logistics. The economic evaluation was rehearsed and estimates of cost-effectiveness made; potential attributes and levels that can form the basis of preference elicitation work in a definitive study were determined. Limitations: The pilot was conducted over a 15-month period only, and bleeding on probing appeared to have floor effects. The number of participating dental practices was a limitation and the recruitment rate was moderate. Conclusions: Non-inferiority, floor effects and moderate recruitment rates suggest that a randomised controlled trial might not be the best evaluative design for a definitive study in this population. The process evaluation identified multiple barriers to the use of dental therapists in 'high-street' practices and added real value. Future work: Quasi-experimental designs may offer more promise for a definitive study alongside further realist evaluation. Trial registration: Current Controlled Trials ISRCTN70032696. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 3. See the NIHR Journals Library website for further project information.